The Effect of Intellectual Capital on The Competitive Advantage: A Case Study In Iraq Communication Firms - Firas Salman Khudhair; Rafiduraidabinti Abdul Rahman; Ahmad Amri Bin Zainal Adnan; Dr. Anmar Adnan Khudhair (Zien Journals, 2022)
The domination of intellectual capital (IC) elements on competitive advantage (CA) in Iraq communication firms are investigated in this study. According to the empirical findings, both structural capital (SC), as well as relational capital (RC) possess a favourable influence on CA. The CA is constituted of 48.4% SC and RC. It is stunning to discover that human capital (HC) has no direct influence on CA. Nevertheless, since HC is entrenched in RC, it is acceptable to assert that it has an indirect and significant impact on CA. Gender, including age, affect the influence of RC on CA. Younger males are the ones who are most affected. The impact of SC is only marginally tempered by gender, with women having a somewhat greater impact than men.
Keywords: Intellectual capital; Human capital; Relational capital; Structural capital